2011
DOI: 10.5402/2011/874596
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Identification of Knee Effusion by Ultrasound

Abstract: Twenty-one fourth-year medical students were given a brief lecture on ultrasound of the knee and fifteen minutes of supervised ultrasound scanning of three cadavers which had been injected with saline to give varying degrees of knee effusions. Each student was then individually observed and required to scan both knees of a cadaver different from the practice cadavers and identify the patella, the femur, the quadriceps tendon and if a suprapatellar effusion was present, and which knee had the larger effusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Although it is difficult to conduct well-controlled education studies with large numbers of students over extended time periods due to the many variables involved, an E-portfolio tracking system should facilitate such studies. In addition, small but well-controlled clinically relevant studies of student application of ultrasound will continue to be part of the ultrasound program [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to conduct well-controlled education studies with large numbers of students over extended time periods due to the many variables involved, an E-portfolio tracking system should facilitate such studies. In addition, small but well-controlled clinically relevant studies of student application of ultrasound will continue to be part of the ultrasound program [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because these students were more comfortable with normal anatomy seen on ultrasound images and preferred to spend more time on pathology and linking patients' clinical presentations to abnormal findings on the images. As a result of this, we advocate for early student exposure to ultrasound as part of their anatomy curriculum, considering the benefits of such exposure in stimulating student interest in medical imaging and anatomy (Teichgraber et al, 1996; Bahner et al, ; Stringer et al, ), improving their confidence and understanding of anatomy (Rao et al, ; Magid et al, ; Brown et al, ; Dreher et al, ) and the acquisition of technical skills (Yoo et al, ; Hoppmann et al, ; Dreher et al, ). However, it would be desirable to also extend ultrasound activities to clinical days to supplement the current program.…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal sonography in medical education is becoming more popular. Hoppman et al [11] demonstrated that after brief ultrasound training, fourth‐year medical students were able to accurately identify knee joint effusions using ultrasound. Shapiro et al [12] demonstrated that basic diagnostic ultrasound skills could be taught to medical students in a relatively short time, with students showing a favorable response to using ultrasound as an adjunct to learning the physical examination.…”
Section: Background and Significancementioning
confidence: 99%